2011
DOI: 10.1097/ajp.0b013e3181f195d3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Chronic Pain and Its Impact on Quality of Life of Patients With HTLV-1-associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP)

Abstract: chronic pain was significantly associated with a higher likelihood of signs/symptoms of anxiety and depression, reflecting a negative impact of pain on patients´ quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 21 publications
(39 reference statements)
3
53
1
2
Order By: Relevance
“…1 Some patients infected with this virus present motor, sensory, and autonomic functional deficits. [6][7][8] One study found that >84.5% of HTLV-1infected patients reported chronic pain, having an incapacitating effect in most of the cases. [6][7][8] One study found that >84.5% of HTLV-1infected patients reported chronic pain, having an incapacitating effect in most of the cases.…”
mentioning
confidence: 99%
“…1 Some patients infected with this virus present motor, sensory, and autonomic functional deficits. [6][7][8] One study found that >84.5% of HTLV-1infected patients reported chronic pain, having an incapacitating effect in most of the cases. [6][7][8] One study found that >84.5% of HTLV-1infected patients reported chronic pain, having an incapacitating effect in most of the cases.…”
mentioning
confidence: 99%
“…It is estimated that more than 100 million Americans have chronic pain [3], and prevalence in other countries varies from about 10-50 % of the general population [4]. Not only is chronic pain a prevalent health issue but it also significantly impacts quality of life [5][6][7][8] and the costs of care, and lost productivity are estimated to total almost $635 billion each year [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than 100 million Americans have chronic pain [3], and prevalence in other countries varies from about 10-50 % of the general population [4]. Not only is chronic pain a prevalent health issue but it also significantly impacts quality of life [5][6][7][8] and the costs of care, and lost productivity are estimated to total almost $635 billion each year [3].Pain guidelines have recommended selfmanagement strategies in the treatment of chronic pain [9,10]. Self management differs from other treatments such as surgery and medication in that it emphasizes the patient's own control over his/her pain experience rather than relying on external factors to treat pain symptoms.…”
mentioning
confidence: 99%
“…Netto and Brites (45) showed that Pilates exercise had no significant difference in the pain dimension of the quality of life. The limitations of this study include the lack of an objective measure of posture and muscle strength, which may explain some of the findings.…”
Section: Discussionmentioning
confidence: 99%